Evaluation Of Time Control Of Drainage Channel Project Using Earned Value Method (Case Study: Rehabilitation of Drainage Channels in Ngronggo Village, Kediri City) - Mukhamad Roichuddin; Olvi Pamadya Utaya Kusuma; Susilowati Susilowati; Monica Dewi (International Journal of Health Engineering and Technology, 2026)
The success of a construction project is influenced by the management of three main components: cost, time, and quality. Time control is an important aspect so that project implementation can run according to the planned schedule. This study aims to evaluate the time performance of the Drainage Channel Rehabilitation Project in Ngronggo Village, Kediri City using the Earned Value method. The Earned Value method is used to analyze project performance by comparing the planned schedule with the work progress that has been achieved during project implementation. The parameters used in this study include the Budgeted Cost of Work Scheduled (BCWS), Budgeted Cost of Work Performed (BCWP), Schedule Variance (SV), and Schedule Performance Index (SPI). The results of the analysis show that the Schedule Variance (SV) value is negative, indicating that the project implementation has been delayed compared to the planned schedule. In addition, the Schedule Performance Index (SPI) value obtained is less than 1 (SPI <1), indicating that the project's time performance is running poorly. Based on the analysis of the estimated project completion time usingEstimate to Completion(ETC) and Estimate At Completion (EAC), the estimated project completion time is 16 weeks, while the project's planned duration is 13 weeks. Therefore, it can be concluded that the project is 3 weeks behind schedule.